In silico Prediction and Exploration of Potential Bacteriocin Gene Clusters Within the Bacterial Genus Geobacillus - Egan, Kevin; Field, Des; Ross, R. Paul; Cotter, Paul D.; Hill, Colin (Frontiers in Microbiology, 2018)
The thermophilic, endospore-forming genus of Geobacillus has historically been associated with spoilage of canned food. However, in recent years it has become the subject of much attention due its biotechnological potential in areas such as enzyme and biofuel applications. One aspect of this genus that has not been fully explored or realised is its use as a source of novel forms of the ribosomally synthesised antimicrobial peptides known as bacteriocins. To date only two bacteriocins have been fully characterised within this genus, i.e., Geobacillin I and II, with only a small number of others partially characterised. Here we bioinformatically investigate the potential of this genus as a source of novel bacteriocins through the use of the in silico screening software BAGEL3, which scans publically available genomes for potential bacteriocin gene clusters. In this study we examined the association of bacteriocin gene presence with niche and phylogenetic position within the genus. We also identified a number of candidates from multiple bacteriocin classes which may be promising antimicrobial candidates when investigated in vitro in future studies.